Expression of PROX‐1 in oral Kaposi's sarcoma spindle cells. (13th June 2013) - Benevenuto de Andrade, Bruno Augusto; Ramírez‐Amador, Velia; Anaya‐Saavedra, Gabriela; Martínez‐Mata, Guillermo; Fonseca, Felipe P.; Graner, Edgard; Paes de Almeida, Oslei
<x xml:space="preserve">Abstract</x> Background The histogenesis of neoplastic spindle cells of Kaposi's sarcoma is still uncertain, but some studies consider it a lymphatic vessel differentiation. Prox‐1 is a nuclear transcription factor that plays a major role during embryonic lymphangiogenesis, and it has been considered a specific and sensitive lymphatic endothelial cell marker. The aim of this study was to determine the expression of Prox‐1 in oral Kaposi's sarcoma comparing the results with oral benign vascular tumors including capillary hemangiomas and pyogenic granulomas. Methods Expression of Prox‐1 and HHV‐8 was evaluated by immunohistochemistry in 30 oral Kaposi's sarcoma, 5 oral capillary hemangiomas, and 10 oral pyogenic granulomas. The labeling index was expressed as the percentage of positive cells for each case studied. Statistical comparison was performed using the Wilcoxon–Mann–Whitney rank sum test. Results Twenty‐eight (93.3%) and 30 oral Kaposi's sarcoma cases were positive for Prox‐1 and HHV‐8, respectively, while all oral benign vascular tumors were negative for these markers. The number of Prox‐1 and HHV‐8 oral Kaposi's sarcoma‐positive cells increased significantly from patch/plaque to nodular histological stages. Conclusion The expression of Prox‐1 in the neoplastic spindle cells supports the view of a lymphatic differentiation in oral Kaposi's sarcoma. Prox‐1 may also be involved in the pathogenesis of oral Kaposi's sarcoma as the number of positive spindle cells increased progressively from patch to nodular stages and could be eventually useful as an additional diagnostic tool for differential diagnosis between oral Kaposi's sarcoma and benign oral vascular lesions.